Effects of plyometric training on different 8-week training intensity distributions in well-trained endurance runners - Filipas, L.; Bonato, M.; Maggio, A.; Gallo, G.; Codella, R. (Scandinavian Journal of Medicine & Science in Sports, 2022)
The aim of this four-armed parallel group randomized-controlled trial was to evaluate if plyometric training could have different effects on running performance and physiological adaptations depending on the training intensity distribution (TID) in an 8-week intervention in endurance athletes. Sixty well-trained male runners (age: 34 ± 6 years, relative VO2peak: 69 ± 3 ml kg-1 min-1) were recruited and allocated to a pyramidal (PYR), pyramidal + plyometric training (PYR + PLY), polarized (POL), and polarized + plyometric training (POL + PLY) periodization. The periodization patterns were isolated manipulations of TID, while training load was kept constant. Participants were tested pre- and post-intervention for body mass, velocity at 2 and 4 mmol·L-1 of blood lactate concentration (vBLa2, vBLa4), absolute and relative VO2peak and 5-km running time trial performance, counter movement jump and squat jump. There were significant group × time interactions for vBla4 (p = 0.0235), CMJ (p = 0.0234), SJ (p = 0.0168), and 5-km running time trial performance (p = 0.0035). Specifically, vBla4 and 5-km running time trial performance showed the largest post-intervention improvements in PYR + PLY (2.4% and 1.6%) and POL + PLY (2.1% and 1.8%), respectively. No significant interactions were observed for body mass, absolute and relative VO2peak, peak heart rate, lactate peak and rating of perceived exertion. In conclusion, an 8-week training periodization seems to be effective in improving performance of well-trained endurance runners. Including plyometric training once a week appeared to be more efficacious in maximizing running performance improvements, independently from the TID adopted.